Infusing moral content into primary school English textbooks: A critical discourse analysis - Sulistiyo, Urip; Supiani, S.; Kailani, Ahmad; Lestariyana, Reni Puspitasari Dwi (Universitas Pendidikan Indonesia, 2020)
Situated in character-based education, the Indonesian Government mandates all teachers to incorporate moral values into school subjects. Teaching English to young learners (TEYL) is no exception. Little empirical evidence reports how school textbooks (e.g., language textbooks) discursively teach particular values explicitly and implicitly. To validate whether English for young learners (EYL) textbooks teach particular moral values, the present critical discourse study (CDA) reported in this article examines how moral content is discursively infused into EYL textbooks. Framed in Hallidayan Systemic Functional Linguistics (SFL) theory, it looks specifically at how particular moral values are represented in three nationally-adopted EYL textbooks through lexical choices, the representation of images, and selected texts that the textbook writers use to represent their attitudinal discourse. The findings show that the value of helping others is predominantly represented in the textbooks. The other dominant values encapsulated in the textbooks include politeness and caring. We conclude that the textbook writers place greater emphasis on such values as helping others, being polite, and caring in the textbooks in as much as they may want to teach these values at an early age.